Shakespeare in India - Nagarajan, S. 1929-; Viswanathan, S. (Delhi ; New York : Oxford University Press, 1987)
Papers presented at a seminar on William Shakespeare, 1564-1616, and his contemporaries, held at the Department of English, University of Hyderabad, February 1984.
Includes bibliographies.
Robin
Keywords: Shakespeare, William, -- 1564-1616 -- Criticism and interpretation -- Congresses